METHOD FOR SIMULATING ROBOT OPERATION - NAKATANI TAKUYA; MITANI KOICHI; HATAKE KAZUSHI (1996)
PURPOSE: To verify whether a teaching point of a prepared program is desirable or not without actually operating a robot. CONSTITUTION: After the program of a robot to be used in the working of a work is prepared (S1), the propriety of a teaching point is verified by using a robot simulator. A positional deviation allowable area is set around each teaching point defined by the program (S2), a simulation is performed (S3), and whether the positional deviation allowable area is included in the movable range of the robot and the interference with an other member does not exist within the area or not are verified (S4). If any condition is not satisfied, the teaching point is corrected (S8) and a verification is performed again. When it is judged that the teaching point is proper by the simulation, the program having the teaching point is imparted to the robot (S5). After the teaching point is corrected according to the location of the work (S6), the working by the robot is performed (S7).